Effect of a Volleyball Course on Health-Related Fitness Components of University Students - Mohammed Hamdan Hashem Mohammed (Sport Mont, 2018)
Physical educators need to evaluate the physical education (PE) curriculum they provide to their students. One way is through regular health-related fi tness assessments. Physical education programs have improved fi tness levels of schoolchildren, but such data is rare for university students. The aim of this study was to determine the eff ect of a volleyball course on the health-related fi tness of male university students. The participants were non-PE majors from King Fahd University of Petroleum & Minerals. They registered for a volleyball course which was done twice a week for eight weeks (31 October-29 December 2016, 50 minutes per session). The parameters assessed were as follows: 1) body composition through body mass index (BMI), 2) muscular endurance through the 60s curl-up test, 3) fl exibility through the sit and reach test, 4) leg explosive strength through standing long jump, and 5) cardiovascular endurance through a 1.6 km run. Pre and post measurements were taken and the data were analyzed using descriptive statistics and paired t-test with SPSS 16. P-values for statistical signifi cance was set at<0.05 while a Cohen-d>0.2 was considered of practical signifi cance. Data from 145 students were analyzed (mean (SD) age=20.8 (0.64) years). There were improvements from pre to post in all variables except body mass and BMI. The data shows evidence that the volleyball course improved the health-related fi tness variables of the students. This shows a course designed for non-PE majors may improve their fi tness levels if well designed.